Timi Laoye auf einem Pferd (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1958)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Africa; Horses; Horsemanship; Animal sacrifice; Nigeria; Yoruba Art; Royalty